Recommendations for the treatment of hepatitis B in 2017 - Flisiak, Robert; Halota, Waldemar; Jaroszewicz, Jerzy; Juszczyk, Jacek; Małkowski, Piotr; Pawłowska, Małgorzata; Piekarska, Anna; Simon, Krzysztof; Tomasiewicz, Krzysztof; Wawrzynowicz-Syczewska, Marta (Clinical and Experimental Hepatology, 2017)
The therapeutic goal which is currently unfrequent but realistic in HBV infected patients is sustained HBsAg clearance. It is preceded by the loss or significant suppression of HBV replication and leads to inhibition of the progression of liver fibrosis, normalization of biochemical indicators of liver damage, reduction in the risk of hepatocellular carcinoma, prolongation of survival, prevention of HBV infection in the transplanted organ in post-transplant patients, enhancement of the quality of life, inhibition or reversal of extrahepatic changes associated with HBV infection, and halting of the spread of HBV infections. Recommendations of Polish Group of Experts for HBV for 2017 provide guidelines to assess treatment eligibility, choice of the first-line drug, monitoring and duration of treatment, management of treatment failure as well as therapy of HBV associated cirrhosis or hepatocellular carcinoma. Moreover it contains advice for treatment of HBV infection in children, females planning pregnancy or pregnant. We also included recommendations for pre- and post-exposure prophylaxis, prevention of HBV transmission from mother to infant, after liver transplantation, on immunosuppressive therapy and during HCV treatment.